Comparative Analysis of Begonia Plastid Genomes and Their Utility for Species-Level Phylogenetics. - Nicola Harrison; Richard J Harrison; Catherine A Kidner (PLoS ONE)
Recent, rapid radiations make species-level phylogenetics difficult to resolve. We used a multiplexed, high-throughput sequencing approach to identify informative genomic regions to resolve phylogenetic relationships at low taxonomic levels in Begonia from a survey of sixteen species. A long-range PCR method was used to generate draft plastid genomes to provide a strong phylogenetic backbone, identify fast evolving regions and provide informative molecular markers for species-level phylogenetic studies in Begonia.